Compression stiffening of brain and its effect on mechanosensing by glioma cells - Katarzyna Pogoda; LiKang Chin; Penelope C Georges; FitzRoy J Byfield; Robert Bucki; Richard Kim; Michael Weaver; Rebecca G Wells; Cezary Marcinkiewicz; Paul A Janmey (New Journal of Physics, 2014)
Many cell types, including neurons, astrocytes and other cells of the central nervous system, respond to changes in the extracellular matrix or substrate viscoelasticity, and increased tissue stiffness is a hallmark of several disease states, including fibrosis and some types of cancers. Whether the malignant tissue in brain, an organ that lacks the protein-based filamentous extracellular matrix of other organs, exhibits the same macroscopic stiffening characteristic of breast, colon, pancreatic and other tumors is not known. In this study we show that glioma cells, like normal astrocytes, respond strongly in vitro to substrate stiffness in the range of 100 to 2000 Pa, but that macroscopic (mm to cm) tissue samples isolated from human glioma tumors have elastic moduli in the order of 200 Pa that are indistinguishable from those of normal brain. However, both normal brain and glioma tissues increase their shear elastic moduli under modest uniaxial compression, and glioma tissue stiffens more strongly under compression than normal brain. These findings suggest that local tissue stiffness has the potential to alter glial cell function, and that stiffness changes in brain tumors might arise not from increased deposition or crosslinking of the collagen-rich extracellular matrix, but from pressure gradients that form within the tumors in vivo .